Speaking the Unspeakable: The status of “non-Muslims” in Indonesia - Ahmad, Rumadi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
The citizenship of non-Muslims has long been a matter of debate in Islamic politics (fiqh al-siyasah). The problem arose especially after the new world order in the early 20th century, in which citizenship was no longer based on religion. In the literature of fiqh al-siyasah, the status of non-Muslims is divided into four categories: 1) kafir dhimmi (non-Muslims who receive protection); 2) kafir harbi (infidels who are permissible for an assault); 3) kafir mu'ahad (infidels who are bound by a peace treaty with Muslims); and 4) kafir musta'man (infidels who are given asylum in an Islamic country). This paper discusses one of the dictums of Nahdlatul Ulama (NU) —the largest Islamic organization in Indonesia — which did not situate non-Muslims in the category of infidels as known in Islamic political doctrine. Rather, it considered non-Muslims as citizens. Through direct observation in the process of discussion and relevant data tracing, including debate in the media, this paper argues that NU’s decision on the status of non-Muslim citizens is the extend of post-traditionalism’s Islamic character which perceives non-Muslims as having the same status as Muslims and should not be called infidels. This is the consequence of NU's acceptance toward the nation-state notion that sees the equality of all citizens.